Resistensi Kultural dalam Sastra Anak: Kajian Postkolonial terhadap Biografi Tenas Effendi - Aris, Qori Islami; Syam, Essy (Universitas Lancang Kuning, 2025)
This study examines cultural resistance in children's literature through a postcolonial analysis of